Assessing the consistency of hotspot and hot-moment patterns of wildlife road mortality over time - Santos, Rodrigo Augusto Lima (2017)
Spatial and temporal aggregation patterns of wildlife-vehicle collisions are recurrently used to informwhere and when mitigation measures are most needed. The aim of this study is to assess if such aggre-gation patterns remain in the same locations and periods over time and at different spatial and temporalscales. We conducted biweekly surveys (n = 484) on 114 km of nine roads, searching for road casualties(n = 4422). Aggregations were searched using different lengths of road sections (500, 1000, 2000 m) andtime periods (fortnightly, monthly, bimonthly). Our results showed that hotspots and hot-moments aregenerally more consistent at larger temporal and spatial scales. We therefore suggest using longer roadsections and longer time periods to implement mitigation measures in order to minimize the uncer-tainty. We support this finding by showing that the proportional costs and benefits to mitigate roadkillaggregations are similar when using different spatial and temporal units.